Research on the backbone network cache method based on application-awareness - Chun-jing HAN; Ye YANG; Hong-lei LYU; Jing-guo GE; Tong LI; Yun-jie LIU (Tongxin xuebao)
Based on over 900 million HTTP requests from an ISP backbone network，the HTTP characteristic of different content types from a wide range of perspectives was analyzed，including request composition，size，popularity and temporal dynamics，and an application-aware backbone network cache method was proposed，referred to as AACM.The experiment results show that in the case of a slight increase in cache space，the hit ratio of the online-video increases 15%， and the total source traffic and cache I/O load reduced by about half.